Recent Developments in the Reduction of Oxidative Stress through Antioxidant Polymeric Formulations - Muhammad Shajih Zafar; Alessandra Quarta; Marco Marradi; Andrea Ragusa (MDPI AG, 2019)
Reactive oxygen and nitrogen species (RONS) are produced endogenously in our body, or introduced through external factors, such as pollution, cigarette smoke, and excessive sunlight exposure. In normal conditions, there is a physiological balance between pro-oxidant species and antioxidant molecules that are able to counteract the detrimental effect of the former. Nevertheless, when this homeostasis is disrupted, the resulting oxidative stress can lead to several pathological conditions, from inflammation to cancer and neurodegenerative diseases. In this review, we report on the recent developments of different polymeric formulations that are able to reduce the oxidative stress, from natural extracts, to films and hydrogels, and finally to nanoparticles (NPs).